2018
DOI: 10.1186/s13568-018-0601-8
|View full text |Cite
|
Sign up to set email alerts
|

A co-utilization strategy to consume glycerol and monosaccharides by Rhizopus strains for fumaric acid production

Abstract: The ability of Rhizopus oryzae to produce fumaric acid in the presence of glycerol and/or various monosaccharides as carbon sources was examined for seventeen different strains of this fungi. These strains were tested in shake-flask cultures on media containing glycerol and seven different carbohydrates, including glucose, fructose, galactose, mannose, xylose, arabinose, and rhamnose. An interesting and applicationally useful phenomenon was observed. This work presents a new approach to the conventional microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Similar observations were made for the production of fumaric acid with fungi Rhizopus oryzae [24]. These observed improvements had been attributed to various reasons, including the protective role of glycerol under stress conditions [24] and a higher ratio of intracellular NADH/NAD + in co-utilization of glycerol and sugar [23].…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Similar observations were made for the production of fumaric acid with fungi Rhizopus oryzae [24]. These observed improvements had been attributed to various reasons, including the protective role of glycerol under stress conditions [24] and a higher ratio of intracellular NADH/NAD + in co-utilization of glycerol and sugar [23].…”
Section: Resultssupporting
confidence: 61%
“…For instance, co-utilization of glycerol and monosaccharides in fermentation of Clostridium diolis can increase cell growth and 1,3-propanediol product formation [23]. Similar observations were made for the production of fumaric acid with fungi Rhizopus oryzae [24]. These observed improvements had been attributed to various reasons, including the protective role of glycerol under stress conditions [24] and a higher ratio of intracellular NADH/NAD + in co-utilization of glycerol and sugar [23].…”
Section: Resultsmentioning
confidence: 72%
“…In this case, it becomes possible not only to utilize simultaneously several substrates [WU et al, 2016] , but also to increase overall the cultivation efficiency [PIDHORSKYY et al, 2010;LIU et al, 2020] . To date, there is practically no information in the literature about the use of mixed substrates for the biosynthesis of microbial EPS, although this technique has been successfully used to obtain primary (microbial oils [HASSANPOUR et al, 2019] , α, ω-dicarboxylic acids [CAO et al, 2017] , fumaric acid [KOWALCZYK et al, 2018] , secondary metabolites (polyhydroxyalkanoates [RAY et al, 2018] , natamycin [ZENG et al, 2019] , and fermentation products (n-butanol, 1,3-propanediol [SABRA et al, 2016] , lactic acid [HASSAN et al, 2019] , as well as other practically valuable microbial metabolites. In our previous work this approach was used to increase ethapolan production on the mixture of glucose (molasses) with ethanol, fumarate, or acetate [PIDHORSKYY et al, 2010] .…”
Section: Resultsmentioning
confidence: 99%
“…Organic acid production depends on various factors such as the carbon source utilised by Rhizopus spp., oxygen supply, nitrogen limitation and fungal strain selection [21,33]. Studies have found that several carbon sources (glucose, sucrose, mannose, xylose, fructose, cellobiose, fatty acids and glycerol) can be used as a substrate for lactic acid and fumaric acid production [13,15,21,33,34]. For example, Kenealy et al demonstrated that R. arrhizus produced 97 g L −1 fumaric acid (9.7% w/w) when supplied with 120 g L −1 glucose as a carbon source [35].…”
Section: Treatments Nonpareil Carmelmentioning
confidence: 99%